Crystal structure of (1,3-thiazole-2-carboxylato-κ N)(1,3-thiazole-2-carboxylic acid-κ N)silver(I) - Natthaya Meundaeng (2019)
© Meundaeng et al. 2019. The linear two-coordinate silver (I) complex [Ag(C 4 H 2 NO 2 S)(C 4 H 3 NO 2 S)] or [Ag(2-Htza)(2-tza)] is reported (2-Htza = 1,3-thiazole-2-carboxylic acid). The Ag I ion is coordinated by two heterocyclic N atoms from two ligands in a linear configuration, forming a discrete coordination complex. There is an O - H⋯O hydrogen bond between 2-tza - and 2tzaH of adjacent complexes. The hydrogen atom is shared between the two oxygen atoms. This interaction produces a hydrogen-bonded tape parallel to the [110] direction, which is augmented through intermolecular C - H⋯O hydrogen-bonding interactions between the bound thiazole groups. There is a further rather long Ag⋯O interaction [2.8401 (13) Å, compared with a mean of 2.54 (11) Å for 23 structures in the CSD] that assembles these tapes into columns, between which there are C - H⋯π interactions, leading to the formation of a three-dimensional supramolecular architecture.